The Effect of Interfascial Injection on Obturator Nerve Block Compared with Nerve Stimulating Approach by Ultrasound-Guide: A Randomized Clinical Trial - Kim, Yong Beom; Park, Hee Yeon; Kim, Kyung Mi; Shin, Hyeon Ju; Kim, Su Bin; Lee, Mi Geum (Urology Journal, 2019)
Purpose: This study was conducted to evaluate whether the ultrasound-guided interfascial injection technique is really compatible with the ultrasound-guided nerve stimulating technique for obturator nerve block (ONB) at the inguinal crease after bifurcation of the obturator nerve. Materials and Methods: A total 62 ONBs were performed for transurethral resection of bladder tumors under spinal anesthesia, and divided into two groups, that is, to an ultrasound-guided ONB with nerve stimulation control group (the US-NS group) or an ultrasound-guided interfascial injection experimental group (the US-IFI group). In the US-IFI group, complete ONB was confirmed using a nerve stimulator at 5 min after completing the injection, and if residual twitching remained, another local anesthetic was injected; in such cases blocks were considered to have ‘failed’. During TURB surgeries, two urology assistants determined obturator reflex grade (I-IV) at 15 min after injection completion in both groups. Results: We assumed that the US-NS group achieved complete ONB in all cases. Six cases in the US-IFI group failed to achieve complete ONB (failure rate: 0% versus 19.4%, P = .012). There was one case of grade II obturator reflex in each group. Conclusion: The ultrasound-guided interfascial injection technique was not compatible with the ultrasound-guided nerve stimulating technique for ONB at the inguinal crease.